2007
DOI: 10.1172/jci27095
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent embryonic lethality and exaggerated vascular remodeling in heparin cofactor II–deficient mice

Abstract: atherosclerosis. However, the in vivo effects and the molecular mechanism underlying the action of HCII during vascular remodeling remain elusive. To clarify the role of HCII in vascular remodeling, we generated HCII-deficient mice by gene targeting. In contrast to a previous report, HCII -/-mice were embryonically lethal. In HCII +/-mice, prominent intimal hyperplasia with increased cellular proliferation was observed after tube cuff and wire vascular injury. The number of protease-activated receptor-1-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 63 publications
4
64
0
Order By: Relevance
“…In addition, we and others have recently reported that high plasma HC activity reduced the restenosis of coronary arteries and femoral arteries after stenting 26,45) and attenuated carotid plaque formation 27) in elderly patients. In experimental animal studies using HC -deficient mice, we and Tollefsen's group have shown accelerated vascular remodeling in HC -deficient mice with increased inflammatory cytokines and chemokine gene expression and oxidative stress 29,30) . Taken together, these observations suggest that HC has a pivotal role in protection against "systemic atherosclerosis" in elderly individuals with atherosclerotic risk factors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, we and others have recently reported that high plasma HC activity reduced the restenosis of coronary arteries and femoral arteries after stenting 26,45) and attenuated carotid plaque formation 27) in elderly patients. In experimental animal studies using HC -deficient mice, we and Tollefsen's group have shown accelerated vascular remodeling in HC -deficient mice with increased inflammatory cytokines and chemokine gene expression and oxidative stress 29,30) . Taken together, these observations suggest that HC has a pivotal role in protection against "systemic atherosclerosis" in elderly individuals with atherosclerotic risk factors.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported an elderly woman with congenital HC deficiency who manifested multiple atherosclerotic disorders 25) , and we have reported the results of clinical studies showing that HC can reduce in-stent restenosis after percutaneous coronary intervention and reduce plaque formation in the carotid artery [26][27][28] . Moreover, we and Tollefsen's group have reported that prominently accelerated vascular remodeling, including atherosclerosis, was observed in HC -deficient mice compared to HC wild-type mice 29,30) . These observations suggested a potential role of HC in counteracting the development of PAD by inhibiting thrombin action in peripheral arteries; however, it is unclear whether HC can contribute to reducing the morbidity of PAD.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Enlarged LAV has been shown to be associated with inflammation and atherosclerosis. 26,27 As cuff-tube placement around the femoral artery caused increases in the gene expression levels of inflammatory cytokines and chemokines, such as interleukin-1b and -6 and monocyte chemoattractant protein-1 in HCII-deficient mice compared with the levels in wild-type mice, 14 there is a possibility that HCII prevents LA enlargement partly through its anti-inflammatory potency leading to attenuation of left atrial remodeling. As LAV is an indicator of the burden of diastolic dysfunction, even in patients without atrial fibrillation or significant valvular heart disease, 28 our results indicated that plasma HCII activity could be involved in the pathogenesis of left ventricular diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…As HCII can counteract the actions of thrombin at injured vascular walls, we, and others, have investigated and confirmed the protective role of HCII against atherosclerosis in clinical examinations and studies using HCII-deficient mice. [9][10][11][12][13][14][15] As the development of vascular remodeling, including atherosclerosis, has been shown to be closely associated with cardiac remodeling in humans and experimental animal models, we hypothesized that HCII is involved in the process of not only atherosclerosis, but also cardiac remodeling. In order to clarify this issue, we investigated the relationships between plasma HCII activity and surrogate markers with respect to cardiac remodeling in elderly subjects with cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%